How do you solve #2x  (3/4) + (4/3) = 8 + (4/3)#?
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 2x  (3/4) + (4/3) = 8 + (4/3):

Combine like terms: 2x  (3/4) + (4/3) = 8 + (4/3) 2x  (3/4) + (4/3)  (4/3) = 8 2x  (3/4) = 8

Add (3/4) to both sides: 2x  (3/4) + (3/4) = 8 + (3/4) 2x = 8 + (3/4)

Combine fractions: 2x = (8 * 4/4) + (3/4) 2x = (32/4) + (3/4)

Add fractions: 2x = (35/4)

Divide both sides by 2: x = (35/4) / 2 x = (35/4) * (1/2) x = 35/8
So, the solution is x = 35/8.
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
 98% accuracy study help
 Covers math, physics, chemistry, biology, and more
 Stepbystep, indepth guides
 Readily available 24/7